All-plastic composite toothpaste tube sheet suitable for being recycled and preparation process of all-plastic composite toothpaste tube sheet
By developing organic-inorganic composite modifiers in all-plastic composite toothpaste tube sheets, and using intercalated modified graphene oxide and ethylene-vinyl alcohol copolymer to composite, the problem of reduced mechanical properties and barrier properties of the all-plastic composite toothpaste tube sheets during the thinning process is solved, achieving better performance and suitable for recycling.
Patent Information
- Application Number
- CN202411451522.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-17
AI Technical Summary
During the thinning process of existing all-plastic composite toothpaste tube sheets, the mechanical properties and barrier properties are reduced, affecting the use effect.
A new type of organic-inorganic composite modifier was developed. By synthesizing a single-quaternary ammonium salt intercalator and a biquaternary ammonium salt intercalator, graphene oxide was intercalated and modified, and composited with an ethylene-vinyl alcohol copolymer, and fully plastic composite toothpaste tube sheets suitable for recycling were prepared.
It significantly improves the mechanical properties and barrier properties of the fully plastic composite toothpaste tube sheet, making it more suitable for recycling and excellent performance in the field of toothpaste packaging.
Smart Images

Figure CN119505304A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of toothpaste tube sheets, and in particular to a fully plastic composite toothpaste tube sheet suitable for recycling and a preparation process thereof. Background Art
[0002] At present, the composite packaging sheets used in toothpaste on the market are mainly aluminum-plastic composite sheets and all-plastic composite sheets. The initial thickness of the all-plastic composite sheet is generally around 350μm, and the thickness of the barrier layer EVOH is as high as 25μm. With the development of manufacturing technology, the thickness of the material has gradually decreased from 350μm. The commonly used thickness is now 300μm and 275μm, and the thickness of EVOH has been reduced to 15μm. The reduction in the overall thickness of the sheet will reduce the mechanical properties of the material, which will have a potential impact on the normal use of the material. At the same time, the thinning of the barrier material will also cause a reduction in barrier performance.
[0003] How to ensure the performance of the sheet while reducing the thickness? Thanks to the continuous development of materials science, the development and application of various new barrier materials have solved a series of problems.
[0004] Graphene is a two-dimensional material with an ultra-thin perfect structure. The excellent barrier properties brought by its sheet structure have also attracted people's attention. Studies have shown that even the smallest He atoms cannot pass through a single layer of graphene. However, the preparation conditions of graphene are harsh and the preparation process is complicated, which limits the large-scale production and application of graphene. As a derivative of graphene, graphene oxide has a two-dimensional sheet structure similar to graphene. Although the surface of graphene oxide contains a large number of defects caused by oxygen-containing functional groups, it still has good barrier properties for small molecules. In addition, graphene oxide can be mass-produced by the chemical oxidation process of graphite, which makes it have good application prospects in improving the barrier properties of polymers. Summary of the invention
[0005] The present invention independently develops a new type of organic-inorganic composite modifier, which is used to simultaneously improve the mechanical properties and barrier properties of a single PP material, thereby preparing a fully plastic composite sheet material, which is very suitable for recycling and can be used to manufacture toothpaste tube packaging materials.
[0006] A process for preparing a fully plastic composite toothpaste tube sheet suitable for recycling comprises the following steps:
[0007] Step 1: synthesizing a monoquaternary ammonium salt intercalant and a diquaternary ammonium salt intercalant;
[0008] The chemical structural formula of the monoquaternary ammonium salt intercalant is:
[0009]
[0010] The chemical structural formula of the diquaternary ammonium salt intercalant is:
[0011]
[0012] Step 2: Based on covalent bonding, hydrogen bonding and electrostatic bonding, graphene oxide is intercalated and modified by using a monoquaternary ammonium salt intercalation agent and a diquaternary ammonium salt intercalation agent to obtain intercalation-modified graphene oxide; the intercalation-modified graphene oxide is compounded with an ethylene-vinyl alcohol copolymer to prepare an organic-inorganic composite modifier;
[0013] Step 3: Adding an organic-inorganic composite modifier to a single polypropylene raw material, and adopting a nine-layer co-extrusion blow molding film-forming process to prepare a fully plastic composite toothpaste tube sheet suitable for recycling.
[0014] Preferably, the preparation method of the monoquaternary ammonium salt intercalant is:
[0015] Step S2-1: using a protonic acid catalyst to catalyze a Mannich condensation reaction of α-H-containing paeonol with formaldehyde and dimethylamine to prepare a tertiary amine monomer;
[0016] Step S2-2: Based on the nucleophilic substitution mechanism, the tertiary amine functional group of the tertiary amine monomer undergoes a quaternization reaction with the chlorine functional group of 3-chloropropyltrimethoxysilane to prepare a monoquaternary ammonium salt intercalant.
[0017] Preferably, the protonic acid catalyst is one of sulfuric acid, hydrochloric acid and phosphoric acid.
[0018] Preferably, the preparation method of the diquaternary ammonium salt intercalant is: based on the nucleophilic substitution mechanism, the tertiary amine functional group of the tertiary amine monomer and the chlorine functional group of 1,5-dichloropentane undergo quaternization reaction, and the molar ratio of the tertiary amine monomer to 1,5-dichloropentane is controlled to be (2.01-2.05):1, so as to prepare the diquaternary ammonium salt intercalant.
[0019] Preferably, the method for preparing the fully plastic composite toothpaste tube sheet suitable for recycling in step 3 is:
[0020] Step S5-1: The fully plastic composite toothpaste tube sheet suitable for recycling is set to be a nine-layer co-extruded film, and the film structure thereof is as follows:
[0021] The first layer: a polypropylene resin layer prepared from 100wt% polypropylene resin as raw material, 5 to 15 parts by weight;
[0022] The second layer: a polypropylene resin layer prepared from 100wt% polypropylene resin, 5 to 15 parts by weight;
[0023] The third layer: a bonding layer prepared from 100wt% maleic anhydride grafted polypropylene resin, 3 to 8 parts by weight;
[0024] The fourth layer: a barrier layer prepared from 95-99wt% polypropylene resin and 1-5wt% ethylene-vinyl alcohol copolymer resin, 5-15 parts by weight;
[0025] The fifth layer: a barrier layer prepared from 90-99wt% polypropylene resin and 1-10wt% organic-inorganic composite modifier, 10-50 parts by weight;
[0026] The sixth layer: a barrier layer prepared from 95-99wt% polypropylene resin and 1-5wt% ethylene-vinyl alcohol copolymer resin, 5-15 parts by weight;
[0027] The seventh layer: a bonding layer prepared from 100wt% maleic anhydride grafted polypropylene resin, 3 to 8 parts by weight;
[0028] The eighth layer: a polypropylene resin layer prepared from 100wt% polypropylene resin as raw material, 5 to 15 parts by weight;
[0029] The ninth layer: a polypropylene resin layer prepared from 100wt% polypropylene resin as raw material, 5 to 15 parts by weight;
[0030] Step S5-2: The raw materials in step S5-1 are respectively put into the hoppers of the nine screw extruders of the nine-layer co-extrusion film blow molding unit. After stirring and mixing, the molten resin is converged at the head of the machine through the diverter, extruded and blown through the die head, cooled, and wound to obtain a fully plastic composite toothpaste tube sheet with a thickness of 250-300μm suitable for recycling.
[0031] Preferably, the mass ratio of intercalated modified graphene oxide to ethylene-vinyl alcohol copolymer in the organic-inorganic composite modifier is 1:(1-5);
[0032] Preferably, the mass ratio of the monoquaternary ammonium salt intercalant, the diquaternary ammonium salt intercalant and the graphene oxide in the intercalation modified graphene oxide is 1:1:(1-3).
[0033] Preferably, the graphene oxide has a thickness of 2 to 5 nm and a sheet diameter of 3 to 8 μm.
[0034] The application of a fully plastic composite toothpaste tube sheet suitable for recycling prepared according to the above process in the field of toothpaste packaging.
[0035] Beneficial effects:
[0036] The invention synthesizes a monoquaternary ammonium salt intercalation agent and a diquaternary ammonium salt intercalation agent, and simultaneously utilizes the monoquaternary ammonium salt intercalation agent and the diquaternary ammonium salt intercalation agent to perform intercalation modification treatment on graphene oxide by means of chemical bonding (reaction of silanol with hydroxyl, carboxyl and epoxy), hydrogen bonding and electrostatic action, and then compounds with ethylene-vinyl alcohol copolymer to prepare an organic-inorganic composite modifier;
[0037] An organic-inorganic composite modifier was added to a nine-layer co-extruded film of a single PP material, and a nine-layer co-extrusion blow molding film forming process was adopted to prepare a fully plastic composite toothpaste tube sheet with a thickness of 250-300 μm. The experimental results showed that the fully plastic composite toothpaste tube sheet had very excellent mechanical properties and barrier properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a synthetic route for monoquaternary ammonium salt intercalation agents;
[0039] Figure 2 It is the chemical structural formula of diquaternary ammonium salt intercalant;
[0040] Figure 3 This is a line graph showing the performance test results of all-plastic composite toothpaste tube sheets suitable for recycling. DETAILED DESCRIPTION
[0041] Embodiment 1:
[0042] Preparation of monoquaternary ammonium salt intercalants, such as Figure 1 As shown, the preparation steps are as follows:
[0043] The first step: the proton acid catalyst catalyzes the Mannich condensation reaction of α-H-containing paeonol with formaldehyde and dimethylamine to generate a tertiary amine monomer;
[0044] The protonic acid catalyst is one of sulfuric acid, hydrochloric acid and phosphoric acid; hydrochloric acid is used in this experimental example;
[0045] Step 2: Based on the nucleophilic substitution mechanism, the tertiary amine functional group of the tertiary amine monomer undergoes a quaternization reaction with the chlorine functional group of 3-chloropropyltrimethoxysilane to generate a monoquaternary ammonium salt intercalation agent;
[0046] The specific experimental steps for preparing the monoquaternary ammonium salt intercalant are as follows:
[0047] Under nitrogen protection, 1.7 g of paeonol, 0.3 g of formaldehyde, 0.5 g of dimethylamine and 40 mL of anhydrous ethanol were added to a three-necked flask, stirred at room temperature until all dissolved, and then 5 drops of concentrated hydrochloric acid were slowly added to the three-necked flask, the temperature was raised to 85° C., stirred and refluxed for 4 h, and the solvent was removed by rotary evaporation after cooling to room temperature, filtered, and vacuum dried to obtain a tertiary amine monomer;
[0048] Under nitrogen protection, 1.1 g of tertiary amine monomer and 20 mL of cyclohexane were added to a three-necked flask, heated to 40° C. and stirred until completely dissolved, then 1.0 mL of 3-chloropropyltrimethoxysilane was added dropwise to the three-necked flask, stirred at 40° C. for 8 h, cooled to room temperature and then rotary evaporated to remove the solvent, washed with ethyl acetate, and vacuum dried to obtain a monoquaternary ammonium salt intercalation agent;
[0049] The nuclear magnetic resonance hydrogen spectrum of the monoquaternary ammonium salt intercalant is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.84-0.98 (m, 2H), 1.75-1.82 (m, 2H), 3.30 (s, 6H), 3.34-3.38 (t, 2H), 3.49-3.52(t, 2H), 3.57(s, 9H), 3.79-3.83(t, 2H), 4.07(s, 3H), 6.48-7.27(m, 3H).
[0050] Embodiment 2:
[0051] Prepare a diquaternary ammonium salt intercalant, the chemical structure of which is as follows Figure 2 As shown, the preparation method is as follows: based on the nucleophilic substitution mechanism, the tertiary amine functional group of the tertiary amine monomer reacts with the chlorine functional group of 1,5-dichloropentane to undergo quaternization reaction, and the molar ratio of the tertiary amine monomer to 1,5-dichloropentane is controlled to be (2.01-2.05):1 to generate a diquaternary ammonium salt intercalant, and the specific experimental steps are as follows: under the protection of nitrogen, 2.2g of the tertiary amine monomer and 30mL of cyclohexane are added to a three-necked flask, the temperature is raised to 40°C and stirred until all dissolved, then 0.6mL of 1,5-dichloropentane is added dropwise to the three-necked flask, the temperature is maintained at 40°C and stirred for 12h, the solvent is removed by rotary evaporation after cooling to room temperature, the mixture is washed with ethyl acetate, and vacuum dried to obtain a diquaternary ammonium salt intercalant;
[0052] The nuclear magnetic resonance hydrogen spectrum of the diquaternary ammonium salt intercalant is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 1.60-1.65 (m, 6H), 3.31 (s, 12H), 3.33-3.37 (t, 4H), 3.52-3.56 (t, 4H), 3.74-3.78 (t, 4H), 4.04 (s, 6H), 6.49-7.37 (m, 6H).
[0053] Embodiment 3:
[0054] Prepare modified graphene, the preparation method of which is: use a monoquaternary ammonium salt intercalation agent and a diquaternary ammonium salt intercalation agent to perform intercalation modification treatment on graphene oxide to obtain modified graphene, and the specific experimental steps are: add 3g of nano graphene oxide powder, 80mL of anhydrous ethanol and 20mL of deionized water into a beaker, ultrasonicate for 30min, heat to 40°C and stir and disperse for 2h, then add 1g of monoquaternary ammonium salt intercalation agent and 1g of diquaternary ammonium salt intercalation agent into the beaker, continue to heat to 70°C and stir to react for 4h, filter while hot, wash with anhydrous ethanol until no precipitation is detected in a silver nitrate solution, and vacuum dry to obtain modified graphene;
[0055] Among them, nano graphene oxide powder was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a thickness of 2 to 5 nm and a sheet diameter of 3 to 8 μm;
[0056] An organic-inorganic composite modifier is prepared, and the preparation method thereof is as follows: the modified graphene is uniformly dispersed in an ethylene-vinyl alcohol copolymer matrix to prepare the organic-inorganic composite modifier, and the specific experimental steps are as follows: 15 g of ethylene-vinyl alcohol copolymer and 5 g of modified graphene are added into a twin-screw extruder, and the mixture is blended, melted, extruded, and pelletized through the twin-screw extruder to prepare the organic-inorganic composite modifier;
[0057] The process parameters of the twin-screw extruder are set as follows: the temperatures of zones 1-3 are 160°C, 180°C, and 205°C, respectively, and the rotation speed is 50 r / min.
[0058] Embodiment 3:
[0059] Preparation of a fully plastic composite toothpaste tube sheet suitable for recycling comprises the following steps:
[0060] Step 1: The fully plastic composite toothpaste tube sheet suitable for recycling is set as a nine-layer co-extruded film, and its film structure is as follows:
[0061] The first layer: a polypropylene resin layer prepared with 100wt% polypropylene resin as raw material, 10 parts by weight;
[0062] The second layer: a polypropylene resin layer prepared from 100wt% polypropylene resin as raw material, 10 parts by weight;
[0063] The third layer: a bonding layer prepared from 100 wt% maleic anhydride grafted polypropylene resin, 5 parts by weight;
[0064] The fourth layer: a barrier layer prepared from 97wt% polypropylene resin and 3wt% ethylene-vinyl alcohol copolymer resin, 10 parts by weight;
[0065] The fifth layer: a barrier layer prepared from 95wt% polypropylene resin and 5wt% organic-inorganic composite modifier, 30 parts by weight;
[0066] The sixth layer: a barrier layer prepared from 97wt% polypropylene resin and 3wt% ethylene-vinyl alcohol copolymer resin, 10 parts by weight;
[0067] The seventh layer: a bonding layer prepared from 100wt% maleic anhydride grafted polypropylene resin, 5 parts by weight;
[0068] The eighth layer: a polypropylene resin layer prepared with 100wt% polypropylene resin as raw material, 10 parts by weight;
[0069] The ninth layer: a polypropylene resin layer prepared from 100wt% polypropylene resin as raw material, 10 parts by weight;
[0070] Step 2, respectively putting the raw materials in step 1 into the hoppers of nine screw extruders of a nine-layer co-extrusion film blow molding unit, after stirring and mixing, the molten resin is merged at the head of the die through a diverter, extruded and blown through a die head, cooled, and rolled to obtain a fully plastic composite toothpaste tube sheet suitable for recycling with a thickness of 280 μm;
[0071] The process parameters of the screw extruder corresponding to the polypropylene resin layer are set as follows: the temperatures of zones 1-3 are 120°C, 140°C, and 165°C, respectively; the flow channel temperature is 160°C; and the rotation speed is 30r / min;
[0072] The process parameters of the screw extruder corresponding to the bonding layer were set as follows: the temperatures of zones 1-3 were 115°C, 145°C, and 160°C, respectively, the flow channel temperature was 150°C, and the rotation speed was 15 r / min;
[0073] The process parameters of the screw extruder corresponding to the barrier layer were set as follows: the temperatures of zones 1-3 were 130°C, 160°C, and 180°C, respectively, the flow channel temperature was 175°C, and the rotation speed was 40 r / min;
[0074] Among them, polypropylene resin was purchased from Shanghai Qiaowei Chemical Technology Co., Ltd. with the brand name HJ4012; maleic anhydride grafted polypropylene resin was purchased from Coais Chemical Co., Ltd. with the brand name B1; ethylene-vinyl alcohol copolymer resin was purchased from Dongguan Kaisi Li Plastic Raw Materials Co., Ltd. with the brand name E105B.
[0075] Comparative Example:
[0076] Preparation of sheet a: Only the organic-inorganic blended modifier is used to replace the organic-inorganic composite modifier in the all-plastic composite toothpaste tube sheet suitable for recycling, and the rest of the parts are the same to prepare sheet a, which is used as comparative example 1;
[0077] The preparation steps of the organic-inorganic blend modifier refer to the preparation experiment of the organic-inorganic composite modifier, and the difference is only that: the intercalated modified graphene oxide is replaced by nano graphene oxide powder;
[0078] Preparation of sheet b: Only ethylene-vinyl alcohol copolymer resin is used to replace the organic-inorganic composite modifier in the all-plastic composite toothpaste tube sheet suitable for recycling, and the rest of the parts are the same, to prepare sheet b, which is used as comparative example 1.
[0079] Performance Test:
[0080] (1) The oxygen permeability test and water vapor permeability test of the samples were carried out in accordance with GB / T 1038-2000 and GB / T 1037-2021 respectively. The specific test steps are as follows: a 30 cm round sample was placed in a glass desiccator at an ambient temperature of 25°C and anhydrous calcium chloride was used as a desiccant for 72 hours. Then, the barrier properties of the sample were tested using a Y110 oxygen permeability tester and a TC-03 water vapor permeability tester;
[0081] (2) The tensile strength of the sample was tested using an Instron 5565 universal tensile testing machine. The specific test steps were as follows: a 150 mm × 20 mm sample was fixed on the tensile testing machine, and a tensile test was performed at a tensile rate of 5 mm / min. The longitudinal and transverse tensile strengths of the sample were recorded.
[0082] The above experimental results are shown in Table 1 and Figure 3 .
[0083] Table 1 Performance test results of all-plastic composite toothpaste tube sheets suitable for recycling
[0084]
[0085] The hygienic properties of the samples were tested according to GB / T 5009.60-2003 "Analysis Method for Hygienic Standards of Polyethylene, Polystyrene and Polypropylene Molded Products for Food Packaging". The experimental results confirmed that the fully plastic composite toothpaste tube sheet suitable for recycling prepared by the present invention can meet the requirements of the hygienic standards.
[0086] By comprehensively analyzing the above experimental results, the following conclusions can be drawn:
[0087] (1) The addition of graphene oxide can enhance the barrier and mechanical properties of the sheet;
[0088] (2) The intercalation modification of graphene oxide using monoquaternary ammonium salt intercalation agent and diquaternary ammonium salt intercalation agent and then compounding with ethylene vinyl alcohol copolymer can significantly improve the barrier properties and mechanical properties of the sheet, which is significantly better than the nano graphene oxide powder that has not been intercalated.
Claims
1. A process for preparing a fully plastic composite toothpaste tube sheet suitable for recycling, characterized in that: The steps include: Step 1: synthesizing a monoquaternary ammonium salt intercalant and a diquaternary ammonium salt intercalant; The chemical structural formula of the monoquaternary ammonium salt intercalant is: The chemical structural formula of the diquaternary ammonium salt intercalant is: Step 2: Based on covalent bonding, hydrogen bonding and electrostatic bonding, graphene oxide is intercalated and modified by using a monoquaternary ammonium salt intercalation agent and a diquaternary ammonium salt intercalation agent to obtain intercalation-modified graphene oxide; the intercalation-modified graphene oxide is compounded with an ethylene-vinyl alcohol copolymer to prepare an organic-inorganic composite modifier; Step 3: Adding an organic-inorganic composite modifier to a single polypropylene raw material, and adopting a nine-layer co-extrusion blow molding film-forming process to prepare a fully plastic composite toothpaste tube sheet suitable for recycling.
2. The process for preparing a fully plastic composite toothpaste tube sheet suitable for recycling according to claim 1, characterized in that: The preparation method of the monoquaternary ammonium salt intercalant is as follows: Step S2-1: using a protonic acid catalyst to catalyze a Mannich condensation reaction of α-H-containing paeonol with formaldehyde and dimethylamine to prepare a tertiary amine monomer; Step S2-2: Based on the nucleophilic substitution mechanism, the tertiary amine functional group of the tertiary amine monomer undergoes a quaternization reaction with the chlorine functional group of 3-chloropropyltrimethoxysilane to prepare a monoquaternary ammonium salt intercalant.
3. The process for preparing a fully plastic composite toothpaste tube sheet suitable for recycling according to claim 2, characterized in that: The protonic acid catalyst is one of sulfuric acid, hydrochloric acid and phosphoric acid.
4. The process for preparing a fully plastic composite toothpaste tube sheet suitable for recycling according to claim 1, characterized in that: The preparation method of the diquaternary ammonium salt intercalant is as follows: based on the nucleophilic substitution mechanism, a tertiary amine functional group of a tertiary amine monomer and a chlorine functional group of 1,5-dichloropentane undergo a quaternization reaction, and the molar ratio of the tertiary amine monomer to the 1,5-dichloropentane is controlled to be (2.01-2.05):1, so as to prepare the diquaternary ammonium salt intercalant.
5. The process for preparing a fully plastic composite toothpaste tube sheet suitable for recycling according to claim 1, characterized in that: The preparation method of the fully plastic composite toothpaste tube sheet suitable for recycling in step 3 is: Step S5-1: The fully plastic composite toothpaste tube sheet suitable for recycling is set to be a nine-layer co-extruded film, and the film structure thereof is as follows: The first layer: a polypropylene resin layer prepared from 100wt% polypropylene resin as raw material, 5 to 15 parts by weight; The second layer: a polypropylene resin layer prepared from 100wt% polypropylene resin, 5 to 15 parts by weight; The third layer: a bonding layer prepared from 100wt% maleic anhydride grafted polypropylene resin, 3 to 8 parts by weight; The fourth layer: a barrier layer prepared from 95-99wt% polypropylene resin and 1-5wt% ethylene-vinyl alcohol copolymer resin, 5-15 parts by weight; The fifth layer: a barrier layer prepared from 90-99wt% polypropylene resin and 1-10wt% organic-inorganic composite modifier, 10-50 parts by weight; The sixth layer: a barrier layer prepared from 95-99wt% polypropylene resin and 1-5wt% ethylene-vinyl alcohol copolymer resin, 5-15 parts by weight; The seventh layer: a bonding layer prepared from 100wt% maleic anhydride grafted polypropylene resin, 3 to 8 parts by weight; The eighth layer: a polypropylene resin layer prepared from 100wt% polypropylene resin as raw material, 5 to 15 parts by weight; The ninth layer: a polypropylene resin layer prepared from 100wt% polypropylene resin as raw material, 5 to 15 parts by weight; Step S5-2: The raw materials in step S5-1 are respectively put into the hoppers of the nine screw extruders of the nine-layer co-extrusion film blow molding unit. After stirring and mixing, the molten resin is converged at the head of the machine through the diverter, extruded and blown through the die head, cooled, and wound to obtain a fully plastic composite toothpaste tube sheet with a thickness of 250-300μm suitable for recycling.
6. The process for preparing a fully plastic composite toothpaste tube sheet suitable for recycling according to claim 1, characterized in that: The mass ratio of intercalated modified graphene oxide to ethylene-vinyl alcohol copolymer in the organic-inorganic composite modifier is 1:(1-5); The mass ratio of the monoquaternary ammonium salt intercalant, the diquaternary ammonium salt intercalant and the graphene oxide in the intercalation modified graphene oxide is 1:1:(1-3).
7. The process for preparing a fully plastic composite toothpaste tube sheet suitable for recycling according to claim 6, characterized in that: The graphene oxide has a thickness of 2 to 5 nm and a sheet diameter of 3 to 8 μm.
8. A fully plastic composite toothpaste tube sheet suitable for recycling prepared by the process according to any one of claims 1 to 7, characterized in that: Application of the all-plastic composite toothpaste tube sheet in the field of toothpaste packaging.
Citation Information
Patent Citations
Method for preparing quaternary ammonium salt group-loading graphene oxide material prepared by two-step method, and applications thereof
CN110586034A
Preparation method of graphene polyethylene composite pipe
CN112457506A
Biodegradable composite modified film bag particle material and preparation method thereof
CN113773559A
Antibacterial coating for surface protection of stainless steel structure
CN114989652A
Graphene oxide having antimicrobial properties, preparation process and use thereof to confer antimicrobial properties to rubber articles
US20240132359A1